Mapping attitudes towards the European Union: a comparative analysis among European citizens of 27 member states - Köngeter, Anja (2013)
The European Union’s growing range of competences increases the degree of required societal support among the member states’ citizens. This study intends to ‘map’ national attitudes towards the EU and to deduct their political implications. Therefore, the concepts of i) identification with the EU and ii) support of the EU are combined within a matrix of four ideal types. Individuals are assigned to these four ideal types: the ‘EU-Enthusiasts’, the ‘EU-Pragmatics’, the ‘sceptical EU-Idealists’, and the ‘EU-Opponents’/’EU-Non-affected’. I claim that the population share of the two ‘mixed’ ideal types - mostly neglected in the literature – provide essential insight into national attitude towards the EU: ‘sceptical EU-Idealists’ identify themselves as citizens of the EU but are critical towards its politics; on the other hand, ‘EU-Pragmatics’ support the EU’s politics but do not identify with its institutions or its community. The study’s main finding is the enormous country-specific variation of i) the populations’ ideal type shares and ii) correlations between identification with and support of the EU (Euroba-rometer 77.3, May 2012). Another crucial result is the (partial) rejection of the explanatory macro variable ‘duration of EU membership’. Beyond this, the geographic split-up seems inappropriate: the often assumed idea of pragmatic ‘Eastern’ and idealistic ‘Western’ countries cannot be affirmed, which calls for a change of mind with respect to ‘East-West’ and ‘old-new’ prejudices in this scientific field.
Gesehen am 25.07.2016
Keywords: Hochschulschrift